Ticumbi, entre o Congo e o Bamba : ambiguidades e significados deste Folguedo no triênio 2006-2008 - Queiroz, Monika Mello (2008)
This thesis intends to approach a tradition that if became emblematic in the Espirito Santo, arguing the implicit meanings in all scenic stage of a folcklore dance. The object of the present research consists exclusively of the Ticumbi practised for a composed community for blacks of the city of Conceição of the Barra Espirito Santo. It is considered to carry through a reading politics of this folguedo, while social practical one guided by an ample specter of representations concerning the elements that join the responsible community for the dance one. It fulfills the challenge to understand the place of personages, musics and the dances as attributes of fortalecimento of a group identity where each one of these elements receives a assignment, folloied of certain always transparent characterizations nor to that they do not belong to the field of that one practical. This research meets, thus, inserted in the field that if it stipulated to call history of the present time, assaying the relations between memory and History, and aid in the construction of the actors of its proper identity, opposing the relations between passed and present.